MR Spectroscopy of the Fetal Brain: Is It Possible without Sedation? - Berger-Kulemann, V. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: The quality of spectroscopic studies may be limited because of unrestricted fetal movement. Sedation is recommended to avoid motion artefacts. However, sedation involves side effects. The aim of this study was to assess the feasibility and quality of brain (1)H-MR spectroscopy in unsedated fetuses and to evaluate whether quality is dependent on the type of spectra, fetal presentation, GA, and/or fetal pathology. MATERIALS AND METHODS: Seventy-five single-voxel spectroscopic studies of the fetal brain, performed at gestational weeks 19–38 at 1.5T, were evaluated retrospectively. A PRESS (TE = 144 or 35 ms) was used. Fetal presentation, GA, and kind of pathology were recorded. The quality of the spectra was assessed by reviewing the spectral appearance (line width, signal-to-noise) of the creatine resonance obtained relative to concentrations (ratios-to-creatine) of choline, myo-inositol, and NAA. RESULTS: Of 75 studies, 50 (66.6%) were rated as readable: short TE = 17/50 (34%), long TE = 33/50 (66%), cephalic presentation in 36/50 (72%) studies, breech in 10/50 (20%) studies, and “other” presentation in 4/50 (8%) studies (mean GA, 31.0 weeks). Twenty-eight of 50 fetuses (56%) showed normal development (short TE = 12/28, long TE = 16/28), and 22/50 (44%) showed pathology. Of the 75 studies, 25 (33.3%) were not readable: short TE = 14/25 (56%), long TE = 11/25 (44%), cephalic presentation in 20/25 (80%) studies, breech in 4/25 (16%) studies, and other presentation in 1 study (4%) (mean GA, 30.1 week). Thirteen of 25 fetuses (52%) showed normal development; 12/25 (48%) showed pathology. Statistical analysis revealed no impact of the different parameters on the quality of spectra. CONCLUSIONS: Single-voxel spectroscopy can be performed in approximately two-thirds of unsedated fetuses, regardless of the type of spectra, fetal presentation, GA, and pathology.